ReMoFP: A Tool for Counting Function Points from UML Requirement Models. (14th April 2011) - Batista, Vitor A.; Peixoto, Daniela C. C.; Borges, Eduardo P.; Pádua, Wilson; Resende, Rodolfo F.; Pádua, Clarindo Isaías P. S.
Abstract : Function Point Analysis (FPA) is a widely used technique for measuring software size. It measures software functionality from the user's perspective, usually based on a requirements description. In many software processes, these requirements are represented by UML models. Although there have been attempts to automate the measurement process, FPA counting requires a considerable amount of interpretation which, to be reliable, should be made by experts. On the other hand, fully manual counting methods usually fail to keep synchronized with the requirements model, since requirements frequently change during the development cycle. This paper describes an approach for counting FPA and a compliant tool. This approach makes use of UML requirement models. The tool, called ReMoFP ( Requirement Model Function Point counter ), leaves all the counting decisions to the analyst, but supports him by ensuring consistency with the requirements represented in the models. The ReMoFP was developed by a software development laboratory in Brazil, and helped it to improve counting productivity, consistency, and maintainability.